KEBIASAAN MAKAN DAN MAKANAN IKAN KELABAU (Osteochilus melanopleura) DI SUNGAI SAMIH DESA KUMPANG TENGAH KECAMATAN SEBANGKI KABUPATEN LANDAK - Wati, Kristina Eka; Soetigynya, Widadi Padmarsari; Anzani, Yunita Magrima (Jurnal Sains Pertanian Equator, 2025)
Samih River, located in Kumpang Tengah Village, Sebangki District, Landak Regency, is widely utilized by the local community for various activities, including excessive fishing. This activity has caused a decline in the population of economically valuable fish species, namely the kelabau fish (Osteochilus melanopleura). This study was conducted to analyze the feeding habits and diet of kelabau fish in Kumpang Tengah Village, Sebangki District, Landak Regency, from January to March 2025, consisting of three research stations based on environmental conditions. Kelabau fish were collected using gill nets and fishing lines, and data analysis was carried out using the Index of Preponderance (IP), the Index of Stomach Content (ISC), and relative gut length. The results showed that the main food of kelabau fish was phytoplankton with an IP value of 98.25%, followed by supplementary foods such as aquatic plants and zooplankton with IP values of 1.74% and 0.014%, respectively. Kelabau fish are herbivorous, as indicated by the relative gut length (ISC) values found: 1.232% at station three, 1.081% at station two, and 0.980% at station one.